Effects of Intra-Articular Stromal Vascular Fraction Injection on Clinical Symptoms and Cartilage Health in Osteoarthritic Knees: A Single-Center Pilot Study - Chun-Ru Lin; Chia-Nan Lin; Chung-Chen Lee; Yong-Chen Chen; Yu-Jen Chen; Ming-Hao Chen; Yu-Chih Lin; Shu-Hao Chang (Life)
Osteoarthritis (OA) is a prevalent form of arthritis worldwide. Intra-articular stromal vascular fraction (SVF) injections are a potential therapeutic option for patients with OA. This study aims to assess the effects of intra-articular SVF injections on knee OA. Ten patients with knee OA participated in this study. After administering them with intra-articular SVF injections, their outcomes were evaluated using various questionnaires. MRI T2 mapping was conducted and compared before the intervention and 6 months after. All the data underwent analysis using various tests. Significant differences were observed in the change of Western Ontario and McMaster Universities Arthritis Index, VAS, and Knee Injury and Osteoarthritis Outcome Score between pre-intervention and 6 months post-intervention. The T2 values were significantly lower in the anterior superficial layer of the medial femoral cartilage and middle superficial layer of the lateral femoral cartilage. However, no positive effects were observed in any other regions of the knee cartilage. This study revealed significant differences between the pre- and 6-month post-intervention questionnaires. However, the T2 values did not show consistent changes across all regions of the knee cartilage. Despite positive effects in two regions, the degenerative process appeared to continue in other regions during the tracking period.